Structure and Dynamics of a Promiscuous Xanthan Lyase from Paenibacillus nanensis and the Design of Variants with Increased Stability and Activity. Issue 2 (21st February 2019) - Jensen, Pernille Foged; Kadziola, Anders; Comamala, Gerard; Segura, Dorotea R.; Anderson, Lars; Poulsen, Jens-Christian N.; Rasmussen, Kim Krighaar; Agarwal, Shilpi; Sainathan, Rajendra K.; Monrad, Rune Nygaard; Svendsen, Allan; Nielsen, Jens Erik; et al.
Summary: We have characterized the structure and dynamics of the carbohydrate-modifying enzyme Paenibacillus nanensis xanthan lyase (PXL) involved in the degradation of xanthan by X-ray crystallography, small-angle X-ray scattering, and hydrogen/deuterium exchange mass spectrometry. Unlike other xanthan lyases, PXL is specific for both unmodified mannose and pyruvylated mannose, which we find is correlated with structural differences in the substrate binding groove. The structure of the full-length enzyme reveals two additional C-terminal modules, one of which belongs to a new non-catalytic carbohydrate binding module family. Ca 2+ are critical for the activity and conformation of PXL, and we show that their removal by chelating agents results in localized destabilization/unfolding of particularly the C-terminal modules. We use the structure and the revealed impact of Ca 2+ coordination on conformational dynamics to guide the engineering of PXL variants with increased activity and stability in a chelating environment, thus expanding the possibilities for industrial applications of PXL. Graphical Abstract: Highlights: The crystal structure of full-length Paenibacillus nanensis xanthan lyase was solved The solution structure was investigated by small-angle X-ray scattering The conformational impact of Ca 2+ was revealed by HDX-MS Xanthan lyase variants with improved stability were designed and produced Abstract : Jensen et al. describe the full-length structure and solution-phase dynamics of a xanthan lyase (PXL), an enzyme participating in degradation of the industrial heteropolysaccharide, xanthan. Insights into the structure and the impact of chelating agents on PXL dynamics are used to produce PXL variants with improved activity and stability.